A review of structural material requirements and choices for nuclear power plant - Ortner, Susan (Frontiers in Nuclear Engineering, 2023)
A nuclear power plant is a highly complex installation. Its design is a response to many drivers, including neutronic efficiency, thermal efficiency, economic efficiency, radiation safety, structural integrity, ease of monitoring and maintenance. The correct selection of structural materials has been key in achieving long term structural integrity, as different plant designs and operating conditions impose different combinations of requirements on the materials. This paper describes the reasoning behind structural materials choices and the changing perspectives on the interplay with other design imperatives in historic, current and future plant designs. It also describes the campaigns of materials development put in place to meet novel materials challenges specific to nuclear plant.